3D-electroanatomical mapping of the left atrium and catheter-based pulmonary vein isolation in pigs: A practical guide - Hertel, Julie Norup; Jerltorp, Kezia; Hansen, Malthe Emil Høtbjerg; Isaksen, Jonas L.; Sattler, Stefan Michael; Linz, Benedikt; Chaldoupi, Sevasti-Maria; Jespersen, Thomas; Saljic, Arnela; Gang, Uffe; Manninger, Martin; Linz, Dominik (Frontiers in Cardiovascular Medicine, 2023)
Aim: To propose a standardised workflow for 3D-electroanatomical mapping guided pulmonary vein isolation in pigs. Material and Methods: Danish female landrace pigs were anaesthetised. Ultrasound-guided puncture of both femoral veins was performed and arterial access for blood pressure measurement established. Fluoroscopy- and intracardiac ultrasound-guided passage of the patent foramen ovale or transseptal puncture was performed. Then, 3D-electroanatomical mapping of the left atrium was conducted using a high-density mapping catheter. After mapping all pulmonary veins, an irrigated radiofrequency ablation catheter was used to perform ostial ablation to achieve electrical pulmonary vein isolation. Entrance- and exit-block were confirmed and re-assessed after a 20-minute waiting period. Lastly, animals were sacrificed to perform left atrial anatomical gross examination. Results: We present data from 11 consecutive pigs undergoing pulmonary vein isolation. Passage of the fossa ovalis or transseptal puncture was uneventful and successful in all animals. Within the inferior pulmonary trunk 2-4 individual veins as well as 1-2 additional left and right pulmonary veins could be cannulated. Electrical isolation by point-by-point ablation of all targeted veins was successful. However, pitfalls including phrenic nerve capture during ablation, ventricular arrhythmias during antral isolation close to the mitral valve annulus and difficulties in accessing right pulmonary veins were encountered. Conclusion: Fluoroscopy- and intracardiac ultrasound-guided transseptal puncture, high-density electroanatomical mapping of all pulmonary veins and complete electrical pulmonary vein isolation can be achieved reproducibly and safely in pigs when using current technologies and a step-by-step approach.